Effect of the microtubule-associated protein tau on dynamics of single-headed motor proteins KIF1A - Sparacino, Javier (2014)
Fil: Sparacino, Javier. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.